2005
DOI: 10.1158/0008-5472.can-05-1698
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inhibition of EGFR, VEGFR, and Platelet-Derived Growth Factor Receptor Signaling Combined with Gemcitabine Produces Therapy of Human Pancreatic Carcinoma and Prolongs Survival in an Orthotopic Nude Mouse Model

Abstract: Although gemcitabine has been approved as the first-line chemotherapeutic reagent for pancreatic cancer, its response rate is low and average survival duration is still only marginal. Because epidermal growth factor receptor (EGFR), vascular endothelial growth factor receptor (VEGFR), and plateletderived growth factor receptor (PDGFR) modulate tumor progression, we hypothesized that inhibition of phosphorylation of all three on tumor cells, tumor-associated endothelial cells, and stroma cells would improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
3
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 40 publications
9
85
3
5
Order By: Relevance
“…Furthermore, ZD6474 significantly potentiated the apoptosis induced by the combined treatment with gemcitabine and ionizing radiation. These results agree with previous studies that reported enhanced apoptotic cell death after combined treatment of ZD6474 with paclitaxel, docetaxel, or oxaliplatin in several cell lines (28,30). In contrast, in the esophageal cell line KYSE30, the sequence of ZD6474 for 48 hours followed by either docetaxel or oxaliplatin for 24 hours produced a marked arrest of cells in G 0 -G 1 phase without induction of apoptosis (30).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, ZD6474 significantly potentiated the apoptosis induced by the combined treatment with gemcitabine and ionizing radiation. These results agree with previous studies that reported enhanced apoptotic cell death after combined treatment of ZD6474 with paclitaxel, docetaxel, or oxaliplatin in several cell lines (28,30). In contrast, in the esophageal cell line KYSE30, the sequence of ZD6474 for 48 hours followed by either docetaxel or oxaliplatin for 24 hours produced a marked arrest of cells in G 0 -G 1 phase without induction of apoptosis (30).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the anti-EGFR antibody cetuximab resulted in an additive effect with gemcitabine in an orthotopic model of pancreatic carcinoma in nude mice (10) and produced 12% partial responses and 63% stable diseases in advanced pancreatic cancer patients (11). Finally, a recent study showed that AEE788, an EGFR/ErbB2 and VEGFR tyrosine kinase inhibitor, in combination with gemcitabine, produced apoptosis and significantly suppressed human pancreatic cancer in nude mice (28).…”
Section: Discussionmentioning
confidence: 99%
“…Pericytes in tumor-associated vessels, but not those in vessels of normal mucosa, are enlarged and they overexpress PDGF-Rb and p-PDGF-Rb. 39 In agreement with earlier reports, 13,31 treatment with imatinib decreased pericyte coverage on tumor-associated endothelial cells in our experimental model. The inhibition of PDGF-R signaling may decrease pericyte recruitment and attachment to endothelial cells and destabilize the tumor vasculature.…”
Section: Discussionsupporting
confidence: 93%
“…The mechanisms of this resistance are not completely understood, but the combination of chemotherapy and radiotherapy with molecular therapy shows promising effects in treatment of PDAC. 30,31 In the current study, silencing of BTF3 using specific siRNA molecules did not result in significant changes in the sensitivity or resistance of Aspc-1 or Capan-1 cells to chemotherapeutic agents or radiotherapy, indicating that BTF3 does not directly influence cell apoptosis and/or cycle arrest in PDAC. It has been shown in other cancer cell types that downregulation of BTF3 is associated with apoptosis, suggesting that the ability of BTF3 to act as an anti-apoptotic factor is dependent on the type of cell or tissue.…”
Section: Discussionmentioning
confidence: 45%